Helicobacter pylori-driven modulation of NK cell expansion, intracellular cytokine expression and cytotoxic activity. Issue 2 (February 2015) - Rudnicka, Karolina; Miszczyk, Eliza; Matusiak, Agnieszka; Walencka, Maria; Moran, Anthony P; Rudnicka, Wiesława; Chmiela, Magdalena
During Helicobacter pylori (Hp) infections, innate immune cells may be positively or negatively modulated by Hp compounds or by Hp-induced cytokines. We have shown previously that the natural cytotoxic activity of PBMC was lower in Hp-infected [Hp(+)] than Hp-uninfected individuals [Hp(−)]. Here, we asked whether the Hp-modulated cytotoxic amplitude is associated with changes in the number of NK cells, their activation or intracellular cytokine expression. Flow cytometry immunophenotyping of PBMC was performed with regard to the surface receptors CD3, CD56 and CD25, and intracellular cytokine expression of IL-2, IFN-γ and IL-10 after in vitro stimulation with Hp glycine acid extract (GE), Hp LPS or standard Escherichia coli LPS . Hp GE-driven enhancement of lymphocyte cytotoxic activity was associated with the expansion of CD3 − CD56 + CD25 + NK cells and the up-regulation of IFN-γ and/or IL-2 synthesis, up to the higher level in Hp(−) than in Hp(+), while Hp LPS-mediated decrease in lymphocyte cytotoxicity was accompanied by the lack of CD3 − CD56 + CD25 + NK propagation, the inhibition of pro-inflammatory cytokine expression and intense expansion of IL-10–producing NK cells. Thus, the cytotoxic and cytokine activities of NK cells were dependent on the type of antigenic challenge and the Hp status, that is, NK cells could be modulated positively by Hp GE Ags and negatively by Hp LPS.